175 Rare Complications and Management of Port Site Hernias (PSH) Following Robotic-Assisted Radical Prostatectomy (RARP). (19th August 2022) - Lau, A; Aseem, R; Shrestha, A
Abstract: Robot-assisted surgery has become increasingly prevalent in surgical practice and is very commonly performed in urological cancers especially of the prostate gland. Robotic surgical techniques are safe and reproducible; however, they have their associated complications. Risk factors such as the nature of cancer, learning curve of the surgery, experience of the surgeon and patient characteristics have been implicated for potential complications. Complications can range from bleeding, infection, bowel injury, ureteric and nerve damage. Port site hernias (PSH) are an infrequent complication with a reported incidence varying from 0.2–4.8%. Although uncommon, they can result in high morbidity due to bowel incarceration and strangulation. We report two cases of PSH from our large district general hospital, both at the supraumbilical port site after robotic assisted radical prostatectomy (RARP). The first case presented with complete evisceration and strangulation of a segment of small bowel and the second with bowel incarceration and small bowel obstruction. Our cases highlight potentially rare but severe complications of RARP that should be promptly recognised and urgently treated to prevent significant patient morbidity and mortality.